2012
DOI: 10.1074/jbc.m112.375014
|View full text |Cite
|
Sign up to set email alerts
|

A Variant of the Breast Cancer Type 2 Susceptibility Protein (BRC) Repeat Is Essential for the RECQL5 Helicase to Interact with RAD51 Recombinase for Genome Stabilization

Abstract: Background:The BRC repeat is essential for BRCA2 to bind RAD51 and promote homologous recombination. Results: A BRC repeat variant is essential for RECQL5 to bind RAD51 and suppress homologous recombination. Conclusion: The BRC repeat can be utilized to either promote or suppress homologous recombination. Significance: Discovery of multiple functions of the BRC repeat is important for understanding regulation of homologous recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 40 publications
5
66
0
Order By: Relevance
“…DSBs are critical DNA lesions that require an immediate cellular response because failure to do so can result in chromosomal rearrangements, genomic instability, and even cell death. It has been shown that RECQL5 interacts with RAD51 to inhibit RAD51-induced D-loop formation and sister chromatid exchange (29). Consistent with that finding, RECQL5 prevents RAD51 single-stranded DNA (ssDNA) filament formation by promoting synthesis-dependent strand annealing to mediate DSB repair (30).…”
supporting
confidence: 64%
“…DSBs are critical DNA lesions that require an immediate cellular response because failure to do so can result in chromosomal rearrangements, genomic instability, and even cell death. It has been shown that RECQL5 interacts with RAD51 to inhibit RAD51-induced D-loop formation and sister chromatid exchange (29). Consistent with that finding, RECQL5 prevents RAD51 single-stranded DNA (ssDNA) filament formation by promoting synthesis-dependent strand annealing to mediate DSB repair (30).…”
supporting
confidence: 64%
“…Srs2‐BRCv structurally resembles the BRC repeat of the human tumour suppressor BRCA2 (Islam et al , 2012) which mediates BRCA2–RAD51 interaction, thereby promoting recruitment of RAD51 to DSBs and regulation of RAD51 recombinase activity (Jensen et al , 2010; Liu et al , 2010; Thorslund et al , 2010). Srs2‐BRCv also promotes Srs2–Rad51 interaction in vitro (Islam et al , 2012). Notably, in our genetic assays, srs2 mutants lacking BRCv, Srs2(1–836), had an intermediate phenotype: they resembled wild type in SSA and BIR but were partially deficient in de novo telomere addition (Fig 8B–D).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a BRC repeat variant, named BRCv, was identified in HsRecQ5, and was shown to be essential for RecQ5 to interact with Rad51. 38) BRC repeats interact with Rad51 and promote homologous recombination by regulating the Rad51 recombinase activity in the tumor suppressor protein Brca2 (breast cancer type 2 susceptibility protein). 39) Exceptionally, only Drosophila RecQ5 contains 2 putative BRCv repeats; whereas BRCv is present as a single copy in RecQ5 from most species.…”
Section: Discussionmentioning
confidence: 99%